Pola Makan dan Tingkat Ansietas pada Pasien Gastroesophageal Reflux Disease: Studi Analitik Cross-Sectional - Eka Hardianti Arafah; Arni AR; Winda Riyanti (Journal Research of Health Administration and Public Health (JRHAPH), 2026)
Gastroesophageal Reflux Disease (GERD) is a digestive system disorder caused by the rise of stomach acid into the esophagus, which can cause symptoms such as heartburn, a burning sensation in the chest, nausea, and a sour taste in the mouth. One factor influencing the occurrence of GERD is irregular eating patterns, and persistent GERD can affect the psychological condition of patients, including anxiety. This study aimed to determine the relationship between eating patterns and anxiety levels among GERD patients in the working area of Tempe Public Health Center, Wajo Regency. This study used a quantitative cross-sectional design. The population consisted of 103 GERD patients, with a sample of 82 respondents selected through purposive sampling. The research instrument consisted of eating pattern and anxiety questionnaires, analyzed using the Spearman Rank test with a significance level of α = 0.05. The results showed that most respondents had poor eating patterns (44 people; 53.7%) and experienced anxiety (60 people; 73.2%). The Spearman Rank test obtained a p-value of 0.001 (<0.05) with a correlation coefficient of 0.355, indicating a significant relationship between eating patterns and anxiety level, with a low strength and positive direction of correlation. This study concludes that there is a relationship between eating patterns and anxiety level among GERD patients in the working area of Tempe Public Health Center, Wajo Regency.